Kleefstra Syndrome—Dental Manifestations and Needs: A Case Report with a Literature Review - Victoria Karlak; Jakub Jankowski; Julia Kolasińska; Kacper Nijakowski (Case Reports in Dentistry)
Kleefstra syndrome (KS) is a rare genetic disorder (prevalence<1/1 000 000) characterised by autistic spectrum disorder (ASD), childhood hypotonia, and seizures. A typical facial appearance includes microcephaly, arched eyebrows, synophrism, hypertelorism, a short nose, midface hypoplasia, prognathism, and tongue protrusion. This case report presents a 19-year-old female with KS from a dentist’s perspective. The patient demonstrates limited mouth opening with a slight deviation of the mandible on the left side. The mandibular prognathism and anterior open bite are visible. A generalised inflammatory gingival enlargement is most likely a response to local irritants like plaque and calculus but is enhanced by the patient’s mouth breathing habit. Also, the tongue is unusually large—macroglossia. Dental anomalies were diagnosed by digital panoramic radiograph, including dilaceration of the maxillary left second premolar and taurodontism. The patient was qualified to be treated under general anaesthesia with multiple extractions, restorations, hygienisation procedures, and tooth remineralisation. This individual should also be considered for orthodontic treatment and an eventual tongue reduction procedure. In the case of KS, multidisciplinary cooperation as well as frequent dental check-ups with fluoride prophylaxis are recommended. Unfortunately, dental treatment is still not an integral part of taking care of disabled children and youth with rare diseases.